Ghrelin: Central and Peripheral Implications in Anorexia Nervosa - Méquinion, Mathieu; Langlet, Fanny; Zgheib, Sara; Dickson, Suzanne; Dehouck, Bénédicte; Chauveau, Christophe; Viltart, Odile (Frontiers in Endocrinology, 2013)
Food intake and associated disorders are gaining large emphasis in our societies due to their dramatic physiological and psychological consequences on health. Chronic food restriction is a major symptom described in restrictive anorexia nervosa (AN) patients. This disease, mostly observed in young women is the third cause of chronic illness in teenagers. It leads to central and/or peripheral reprogramming that permits the organism to endure the reduced energy supplies. These drastic conditions induce severe weight loss, metabolic disturbances, infertility, osteopenia and osteoporosis. Moreover, increasing number of arguments consider AN as an addictive behaviour to food deprivation or weight loss or physical activity, usually associated with mood disorders. This suggests a potential alteration of the central reward system. Significant changes in hormones involved in energy metabolism, regulation of feeding behaviours and bone formation are described in AN patients, but also in animal models presenting a strong face validity. Surprisingly, the plasma levels of ghrelin, an orexigenic hormone, are increased. This hormone acts centrally to modulate food intake, but also peripherally mainly to maintain blood glucose and to regulate gastric motility. Such increase in plasma ghrelin levels seems paradoxical in light of the restrained eating adopted by these AN patients, but adaptive. The aim of this review is to describe the role played by ghrelin in AN focusing on its central vs peripheral action. The chronic food restriction induces both in AN patients and in rodent models a profound alteration in the « ghrelin » signal integration that lead to the development of inappropriate behaviours like hyperactivity or addiction to food starvation and therefore a greater depletion in energy reserves. The question of a transient insensitivity to ghrelin and/or a potential metabolic reprogramming is discussed in regard of new clinical treatments currently investigated.